Pendampingan Petani Melalui Praktek Budidaya padi Rawa di Kelurahan Makbalim Distrik Mayamuk Kabupaten Sorong PBD - Ajang Maruapey; Nurlela Nurlela; Sulaiman Lisaholit; Kharisma D.K Wardani; Wahyu Ryadin (Yayasan Literasi Sains Indonesia, 2023)
Rice cultivation techniques in swampland are one of the important factors in supporting yield productivity and farmer income. Unfortunately, the land has not been optimally optimized because the human resources of farmers are still low. The purpose of mentoring and practicum is to increase shared knowledge between students and farmers regarding swamp rice cultivation techniques properly and correctly. The results of practicum and mentoring activities show that there is real social interaction between students and farmers, where students gain knowledge and field experience. Meanwhile, farmers obtained new information and knowledge related to rice cultivation in swamps.